2017
DOI: 10.1177/1525740117727491
|View full text |Cite
|
Sign up to set email alerts
|

Online Communication Training for Parents of Children With Autism Spectrum Disorder

Abstract: Children with autism spectrum disorder (ASD) show core deficits in social interaction and communication (American Psychiatric Association [APA], 2013). In early childhood, more than half of children with ASD demonstrate limited verbal skills, referred to as complex communication needs (CCN; Anderson et al., 2007), which exacerbate their ability to connect and communicate. Augmentative and alternative communication (AAC), including technologies such as pictures, speech generating devices, and sign language, can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 32 publications
1
10
0
2
Order By: Relevance
“…Also, based on the findings of the treatment fidelity, this study found effective as in other studies developed on the basis of SRSDM (e.g., Almadanı, 2013;Demircan, 2014;Meyers, 2015;Rumsey & Ballard, 1985;Rogers & Graham, 2008;Sperger, 2010). In addition to these, this study's findings have parallel effective results with other studies applied to families of children with different types of disabilities (e.g., Baker & McCurry, 1984;Brown & Woods, 2015;Cosbey & Muldoon, 2017;Douglas et al, 2018;McCathren, 2010). However, it is observed in these studies that focus is on generally non-academic skills such as teaching self-care skills for visually impaired children (Çakmak, 2011), self-care and daily life skills for children with autism spectrum disorder (Cavkaytar & Pollard, 2009), self-care and home skills for children with intellectual disabilities (Cavkaytar, 2007) and verbal communication skills (Kargın, 2004) to children with hearing impairment.…”
Section: Discussion Conclusion and Suggestionssupporting
confidence: 82%
“…Also, based on the findings of the treatment fidelity, this study found effective as in other studies developed on the basis of SRSDM (e.g., Almadanı, 2013;Demircan, 2014;Meyers, 2015;Rumsey & Ballard, 1985;Rogers & Graham, 2008;Sperger, 2010). In addition to these, this study's findings have parallel effective results with other studies applied to families of children with different types of disabilities (e.g., Baker & McCurry, 1984;Brown & Woods, 2015;Cosbey & Muldoon, 2017;Douglas et al, 2018;McCathren, 2010). However, it is observed in these studies that focus is on generally non-academic skills such as teaching self-care skills for visually impaired children (Çakmak, 2011), self-care and daily life skills for children with autism spectrum disorder (Cavkaytar & Pollard, 2009), self-care and home skills for children with intellectual disabilities (Cavkaytar, 2007) and verbal communication skills (Kargın, 2004) to children with hearing impairment.…”
Section: Discussion Conclusion and Suggestionssupporting
confidence: 82%
“…Benefits to online learning include that parents/trainees can complete at a convenient time [ 27 •]. This may be essential for families with multiple children, single parents, or other challenges.…”
Section: Introductionmentioning
confidence: 99%
“…A partir de lo mencionado anteriormente, se ha encontrado estudios, los cuales refieren que muchas de las estrategias y técnicas basadas en el Análisis Conductual Aplicado son las más adecuadas y respaldadas para ser usadas en el sistema de teleasistencia psicológica de niños con TEA, incluyendo las áreas de conducta, aprendizaje y de lenguaje (Douglas et al, 2017;Parsons, 2019;Pennefather et al, 2018;Sandbank et al, 2020;Unholz-Bowden et al, 2020;Vismara et al, 2013). Estos mismos estudios resaltan al análisis funcional de la conducta y la observación conductual como parte de las estrategias y técnicas más utilizadas y eficaces (Tabla 3) para la evaluación no presencial de niños pequeños.…”
Section: Estrategias Y Técnicasunclassified
“…Nota. Esta tabla muestra las principales estrategias y técnicas con evidencia científica para el sistema de teleasistencia (Douglas et al, 2017;Larroy, 2020;Pennefather et al, 2018;Sandbank et al, 2020;Vismara et al, 2013…”
Section: Directricesunclassified